Impact of marketing costs on Airline profits between limitation and risks Emirates Airline Case Study (Journal of Economic Additions, 2020)
This study aimed at finding out the effect of marketing cost on the profit of Emirates airlines, using multiple regression models and taking the profit as a dependent variable, marketing cost, fuel cost and number of passengers as explained variables during the 1993-2019 period. The study found that there is a significant positive relationship between marketing cost and profit of the company, the cost of fuel has a significant negative impact on profit, while the number of passengers have significant   positive effect. The study recommends the company do not exaggerate in marketing cost, because it established an excellence brand in the world and channeling funds to others uses to face increasing competition.Keywords: Marketing cost, Profit, Emirates Airlines, Multiple Regression Model.Jel Classification Codes: L26, L93, M31.